Effect of combined exposure to lead and decabromodiphenyl ether on neurodevelopment of zebrafish larvae. (February 2016) - Zhu, Biran; Wang, Qiangwei; Shi, Xiongjie; Guo, Yongyong; Xu, Tao; Zhou, Bingsheng
Abstract: The effect of combined exposure to decabromodiphenyl ether (BDE-209) and lead (Pb) on neurodevelopment of zebrafish ( Danio rerio ) larvae was investigated. Zebrafish embryos were exposed to Pb (0, 5, 10, 20 µg/L) and BDE-209 (0, 50, 100, 200 µg/L), either alone or in combination (Mix1: 5 + 50 µg/L, Mix2: 10 + 100 µg/L, Mix3: 20 + 200 µg/L) for up to 144 h post-fertilization. Growth of secondary motoneuron axons and expression of genes related to central nervous system development was significantly inhibited in Mix3 co-exposure group. A significant increase in reactive oxygen species (ROS), lipid peroxidation, DNA damage, and perturbation of the antioxidant system was detected in the Mix3 group compared to single-toxicant treatments or control. Depressed locomotor activity was recorded in the Mix2 and Mix3 groups. Addition of N- acetyl cysteine to Mix3 eliminated excessive ROS, and protected against lipid peroxidation, DNA damage, and locomotor dysfunction. Pb uptake was increased in the presence of BDE-209, but BDE-209 bioconcentration and the ability to metabolize BDE-209 were decreased in the presence of Pb. These results suggest that BDE-209 and Pb have a synergistic disruptive effect on neurodevelopment in zebrafish larvae by enhanced generation of ROS, which is a major factor that contributes to developmental neurotoxicity. Highlights: Neurodevelopment in zebrafish larvae was studied. Combined Pb and BDE-209 exposure caused synergistic detrimental effects. Enhanced ROS generation contributed to developmental neurotoxicity.